Recent dioxin contamination from Agent Orange in residents of a southern Vietnam city - Schecter, A; Dai, L C; Päpke, O; Prange, J; Constable, J D; Matsuda, M; Thao, V D; Piskac, A L (Journal of occupational and environmental medicine, 2001)
Marked elevation of dioxin associated with the herbicide Agent Orange was recently found in 19 of 20 blood samples from persons living in Bien Hoa, a large city in southern Vietnam. This city is located near an air base that was used for Agent Orange spray missions between 1962 and 1970. A spill of Agent Orange occurred at this air base more than 30 years before blood samples were collected in 1999. Samples were collected, frozen, and sent to a World Health Organization--certified dioxin laboratory for congener-specific analysis as part of a Vietnam Red Cross project. Previous analyses of more than 2200 pooled blood samples collected in the 1990s identified Bien Hoa as one of several southern Vietnam areas with persons having elevated blood dioxin levels from exposure to Agent Orange. In sharp contrast to this study, our previous research showed decreasing tissue dioxin levels over time since 1970. Only the dioxin that contaminated Agent Orange, 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), was elevated in the blood of 19 of 20 persons sampled from Bien Hoa. A comparison, pooled sample from 100 residents of Hanoi, where Agent Orange was not used, measured blood TCDD levels of 2 parts per trillion (ppt). TCDD levels of up to 271 ppt, a 135-fold increase, were found in Bien Hoa residents. TCDD contamination was also found in some nearby soil and sediment samples. Persons new to this region and children born after Agent Orange spraying ended also had elevated TCDD levels. This TCDD uptake was recent and occurred decades after spraying ended. We hypothesize that a major route of current and past exposures is from the movement of dioxin from soil into river sediment, then into fish, and from fish consumption into people.